A Novel Immunoregulatory PEGylated Poly(glycerol sebacate)/β‐TCP Membrane for Application in Guided Bone Regeneration. Issue 1 (28th November 2021) - Shen, Hongzhou; Zhang, Chenglong; Zhang, Changru; Shi, Jun; Shen, Steve GF.; Yuan, Yuan; Si, Jiawen
Abstract: The recently developed poly(ethylene glycol)ylated poly(glycerol sebacate)/β‐tricalcium phosphate (PEGS/β‐TCP) membrane possesses favorable mechanical properties and excellent osteogenic activity. This study is designed to evaluate the feasibility of applying PEGS/β‐TCP membrane in guided bone regeneration (GBR) through investigating the in vitro and in vivo activities of macrophages promoted by PEGS/β‐TCP membranes during osteogenesis. The behavior of macrophages seeded on PEGS/β‐TCP and PEGS membranes is assessed in terms of cell viability, polarization pattern, and release of inflammatory and osteogenic cytokines. The in vitro osteogenic effect of PEGS/β‐TCP membrane‐associated macrophage polarization is evaluated by incubating mesenchymal stem cells (MSCs) with conditioned medium derived from macrophages stimulated with PEGS/β‐TCP or PEGS membranes. The in vivo correlation between macrophage polarization and PEGS/β‐TCP membrane‐driven osteogenesis is investigated using a rat calvarial defect model. The results show that PEGS/β‐TCP and PEGS membranes are capable of downregulating M1 polarization and upregulating M2 polarization. Compared to the PEGS membrane, the PEGS/β‐TCP membrane can further alleviate local inflammatory response and significantly promote the in vitro osteogenic differentiation of MSCs and in vivo restoration of bone defects. In conclusion, the novel PEGS/β‐TCP membrane can promote the osteogenic commitment of MSCs and restore calvarial bone defects by improving the macrophage polarization pattern. Abstract : The poly(ethylene glycol)ylated poly(glycerol sebacate)/β‐tricalcium phosphate (PEGS/β‐TCP) membrane drives an improved macrophage polarization pattern characterized by downregulated M1 polarization and upregulated M2 polarization, which subsequently results in the alleviated local inflammatory reaction and enhanced bone regeneration. The favorable osteogenic and immunoregulatory properties of PEGS/β‐TCP membrane identify it as a superior choice for clinical application in guided bone regeneration.